Does analytical thinking improve understanding of accumulation? - Baghaei Lakeh, Arash; Ghaffarzadegan, Navid (System dynamics review, 2015)
People have difficulties inferring the behavior of a stock variable from its inflows and outflows. Our goal is to offer low‐cost interventions to help overcome this difficulty. We hypothesize that the failure to understand accumulation relates to the cognitive mode of thinking: if people use their System 2 mode of thinking (analytical thinking), they are more likely to answer stock–flow questions correctly. We conduct an experiment with 400 participants and test effects of two interventions. The study replicates previously observed stock–flow failure and uncovers several variables that can influence subjects' response to the department store task. One particular finding is that having participants answer an analytical question right before the department store task marginally increases their chances of answering stock–flow questions correctly. Copyright © 2015 System Dynamics Society